Influence of hydrothermal pretreatment on acidity and activity of H-GaAlMFI zeolite for the propane aromatization reaction - Choudhary, Tushar V.; Kinage, A.; Banerjee, S.; Choudhary, Vasant R. (Microporous and Mesoporous Materials, 2005)
The acidity and propane aromatization activity of H-GaAlMFI has been investigated subsequent to different hydrothermal (HT) pretreatments. Extensive degalliation of framework Ga occurred during the HT pretreatments; the framework Si/Ga ratio nearly doubled when the steam concentration was increased from 0% to 80%. The extent of degalliation and corresponding loss of strong zeolitic acidity (measured in terms of pyridine chemisorbed at 400 degrees C) was particularly severe at high (> 500 degrees C) temperatures and steam concentrations (> 40 mol%). Framework Al in the GaAlMFI zeolite was found to be very stable; the FW Si/Al ratio did not change to any appreciable extent even after severe HT pretreatments. Each of the HT pretreatment parameters (concentration of steam: 0-80%, HT temperature: 400-600 degrees C and length of HT pretreatment: 0-6 h) showed a profound influence on the propane aromatization activity. The product selectivity was, however, only mildly affected by the HT pretreatments. The following factors were found to be important for high propane aromatization activity (a) strong zeolitic acidity and (b) optimal content/dispersion of the extra-framework Ga species which are formed in situ during the HT pretreatments. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Acidity; aromatic distribution; Ga-based zeolites; hydrothermal treatment and steam; propane aromatization

Influence of PdO content and pathway of its formation on methane combustion activity - Choudhary, Tushar V.; Banerjee, S.; Choudhary, Vasant R. (Catalysis Communications, 2005)
The methane oxidation reaction is known to induce changes in the surface structure and composition of Pd catalysts; making it extremely arduous to relate the methane oxidation activity to specific catalyst properties by conventional methods (continuous flow reactor studies). To circumvent this, methodical pulse reactor studies have been undertaken to obtain correlations between the initial methane combustion activity and the catalyst properties (Pd-0/PdO content and path of PdO formation). While the initial methane combustion activity (at 160-280 degreesC) continuously increased with increasing PdO concentration (0-100%) in the catalyst, it continuously decreased with increasing Pddegrees content (0-100%). Controlled studies were undertaken to obtain catalysts with identical PdO content by two pathways: (i) by controlled partial oxidization of Pd-0/Al2O3 and (ii) by controlled partial reduction of PdO/Al2O3. Interestingly, for a given PdO content, the catalysts obtained by partial oxidation of Pd-0/Al2O3 showed a significantly superior performance to the catalyst obtained by partial reduction of PdO/Al2O3 for all the temperatures investigated. These studies unambiguously show that along with the relative concentration of PdO, the PdO formation pathway is also critical in deciding the methane combustion activity of the catalyst. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Methane combustion; Oxidation; partially oxidized Pd-0/Al2O3; partially reduced PdO/Al2O3; Pd-0/Al2O3; PdO/Al2O3; pulse reaction of methane

Propane conversion to aromatics on highly active H-GaAlMFI: effect of thermal pretreatment - Choudhary, Tushar V.; Kinage, A.; Banerjee, S.; Choudhary, Vasant R. (Energy & Fuel, 2006)
The propane aromatization activity over H-GaAlMFI has been investigated after different thermal pretreatments ( calcination temperature range: 500- 800 degrees C) at a reaction temperature of 500 degrees C and in the space velocity range of 1500-12000 cm(3)/g/h. The calcination temperature had a strong influence on the strong acidity of the zeolite, propane conversion, and aromatic distribution. The decrease in acidity with increased thermal treatment severity correlated well with the decrease in the framework Ga. There was a considerable decrease in propane aromatization activity at calcination temperatures above 600 degrees C. The effect of calcination temperature on the propane aromatization activity can be explained in terms of change in the strong acidity of the zeolite and the extraframework Ga content. The selectivity for aromatics was found to decrease with increasing thermal pretreatment severity, while that for methane, ethane, and propylene was found to increase. The aromatic distribution was also influenced by the thermal pretreatment; the selectivity for benzene increased with increasing pretreatment temperature, while the selectivity for toluene, C-8 aromatics, and C9+ aromatics decreased.

Odd-even alternation in tautomeric porous organic cages with eceptional chemical stability - Bera, S.; Basu, A.; Tothadi, S.; Garai, B.; Banerjee, S.; Vanka, K.; Banerjee, R. (Angewandte Chemie-International Edition, 2017)
Amine-linked (C-NH) porous organic cages (POCs) are preferred over the imine-linked (C= N) POCs owing to their enhanced chemical stability. In general, aminelinked cages, obtained by the reduction of corresponding imines, are not shape-persistent in the crystalline form. Moreover, they require multistep synthesis. Herein, a one-pot synthesis of four new amine-linked organic cages by the reaction of 1,3,5-triformylphloroglucinol (Tp) with different analogues of alkanediamine is reported. The POCs resulting from the odd diamine (having an odd number of -CH2 groups) is conformationally eclipsed, while the POCs constructed from even diamines adopt a gauche conformation. This odd-even alternation in the conformation of POCs has been supported by computational calculations. The synthetic strategy hinges on the concept of Schiff base condensation reaction followed by keto-enol tautomerization. This mechanism is the key for the exceptional chemical stability of cages and facilitates their resistance towards acids and bases.